Electronic and Optical Properties Characterization of MoS2 Two-Dimensional Exfoliated nanomaterials. Issue 47 (21st July 2016) - Fadil, Dalal; Fayaz, Ridwan H.; Kaul, Anupama B.
ABSTRACT: For optoelectronic application, two-dimensional materials such as molybdenum disulfide (MoS2 ) are very promising candidate with their interesting electronic and optical properties. The layered structure of these materials makes them amenable to mechanical exfoliation to form scalable 2D atomic crystals. For width range of applications, liquid phase exfoliation using sonication and centrifugation in appropriate solvent is needed. This simple and scalable technique gives high quality of exfoliation of 2D materials without chemical reactions. In this paper, we report an example of the optical and electronic characterizations on MoS2 synthesized by liquid exfoliation in specific solvent.